Association between Stunting in Children Under Five and Types of Food Sources - Nur Mufida Wulan Sari; Wilis Cahyaning Ayu; Trias Mahmudiono; Mahmudah Mahmudah; RR Soenarnatalina (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
The prevalence of stunting in children under five years old has decreased from 25% in 2013 to 18% in 2019 in The Gambia. The consumption of certain food groups, as part of minimum dietary diversity, serves as a measure of the adequacy of nutrient density for children. This study aims to examine the association between stunted children under five years old and types of food sources, as well as wealth status. Secondary data from The Gambia Demographic and Health Survey 2019-2020 were analyzed, involving 2,533 out of 8,362 children. Logistic regression tests were performed with a 95% confidence interval. Staple foods were identified as the dominant food source for stunted toddlers (p< 0.05; OR = 1.78; 95% CI = 1.436-2.216) and considered a risk factor for stunting. Food intake from more than four food sources (OR = 0.6; 95% CI = 0.403-0.88), place of residence (OR = 0.72; 95% CI = 0.53-0.95), middle wealth status (OR = 0.47; 95% CI = 0.33-0.68), and wealthy household (OR = 0.74; 95% CI = 0.52-1.05) were significantly associated with a reduced likelihood of stunting and considered protective factors. The incidence of stunting is linked to the diversity of food sources given to toddlers. In providing care for stunted toddlers at the community level, stakeholders must consider food diversity, economic capacity, and type of residence.